GENESIS AND EVOLUTION OF THE CONCEPT „POLITICAL OPPOSITION” IN THE POLITICAL AND LEGAL THOGHT - Кашаба, О.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The analysis of political and legal studies gives reason to confirm the presence of a wide range of approaches to the definition of „political opposition". However, the common of these scientific intelligences is to provide the political opposition with a high status, along with the authorities and resting a great responsibility on it for the nature of the political regime and the civility of the political process in the country.